Glial Fibrillary Acidic Protein in Blood as a Disease Biomarker of Neuromyelitis Optica Spectrum Disorders - Kim, Hyunjin; Lee, Eun-Jae; Lim, Young-Min; Kim, Kwang-Kuk (Frontiers in Neurology, 2022)
Glial fibrillary acidic protein (GFAP) is a type III intermediate filament protein found in astrocytes in the brain. Damaged astrocytes release GFAP into cerebrospinal fluid and blood. Thus, GFAP levels in these body fluids may reflect the disease state of neuromyelitis optica spectrum disorder (NMOSD), which includes astrocytopathy, characterized by pathogenic antibodies against aquaporin 4 located on astrocytes. Recently, single-molecule array technology that can detect these synaptic proteins in blood, even in the subfemtomolar range, has been developed. Emerging evidence suggests that GFAP protein is a strong biomarker candidate for NMOSD. This mini-review provides basic information about GFAP protein and innovative clinical data that show the potential clinical value of blood GFAP levels as a biomarker for NMOSD.